Przemoc jako konstytutywny element teorii polityczności. Carl Schmitt a tzw. kwestia żydowska - Slováček, Petr; Rubisz, Lech (Hybris, 2016)
Article deals with the relationship between Carl Schmitt’s political theory and political theology, which inherently works with the violence assumption, and the so called jewish question. Author shows the way the enemy of the political is gradually constructed on the basis of textual and doctrinal analysis. The core of Schmitt’s enemy construction depends on the refusal of the philosophical tradition, which assume that all man are equal as far as they are participating in one common nature or are in actual or potential possesion of reason. This refusal is the basis on which the criticism of normativism, for Schmitt in the inter-war period represented especially by jewish thinkers such as Hans Kelsen, is built to be after 1933 used in open attack on Jews as such.